2015
DOI: 10.1093/ajae/aav005
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' Adaptation to Extreme Weather Events through Farm Management and Its Impacts on the Mean and Risk of Rice Yield in China

Abstract: We explore how rice farmers adjust their farm management practices in response to extreme weather events and determine whether their adjustments affect the mean, risk, and downside risk of rice yield. Based on a survey of 1,653 rice farmers in China, our econometric analyses show that the severity of drought and flood in the study areas significantly increases the risk and downside risk of rice yield. The applied farm management measures respond to severe drought and flood and can be considered as adaptation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 31 publications
6
103
2
1
Order By: Relevance
“…Huang et al . () found that natural disasters had significantly negative effects on the rice yield and that severe floods and drought encourage farmers to improve farm management. Di Falco et al .…”
Section: Sample and Variable Selectionmentioning
confidence: 99%
“…Huang et al . () found that natural disasters had significantly negative effects on the rice yield and that severe floods and drought encourage farmers to improve farm management. Di Falco et al .…”
Section: Sample and Variable Selectionmentioning
confidence: 99%
“…There are multiple approaches being reported to address such relations. For example, survey methodology is helpful to collect first‐hand information of how drought has affected crop yields and how farmers adapted to drought (Chen et al, ; Huang et al, ; Wang et al, ; Yan et al, ). Empirical models have been applied to analyze the statistical relations among meteorological factors and yields (Huang et al, ; Qin et al, ; Zhang & Huang, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rice farmers in China often adjust their farm management practices (e.g., reseeding, fixing, and cleaning seedlings) in response to extreme weather events such as drought and flood (Huang et al, 2015), which can help to stabilize production.…”
Section: Resultsmentioning
confidence: 99%